The Burial of Bukhaef: Discoveries Near the Pyramid of Teti at Saqqara, 2021 - Hawass, Zahi.
The discovery of a yellow/white on black coffin, shabtis, and a fragmentary Book of the Dead papyrus of Bukhaef by the Egyptian Expedition in 2020–2021 from a shaft near the pyramid of Neith in the Teti Pyramid cemetery is discussed. The material dates to the late Eighteenth-early Nineteenth Dynasties.